2011
DOI: 10.1094/pdis-10-10-0750
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Cylindrocarpon pauciseptatum Associated with Grapevine Decline from Castilla y León, Spain

Abstract: During a survey for grapevine decline, 10 young grapevines (cvs. Tempranillo and Verdejo) with low vigor and little foliage were collected between June 2008 and August 2009. Small pieces of vascular and brown wood were placed onto malt extract agar supplemented with 0.25 g/liter of chloramphenicol and incubated at 25°C. Fifteen resulting colonies were transferred to potato dextrose agar in petri dishes (90 mm). Colonies with white mycelium covered the dishes after 10 days of incubation at 25°C in darkness; myc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 0 publications
1
35
0
3
Order By: Relevance
“…The purpose of this treatment was to hasten the onset of symptoms since one of the biggest disadvantages in the analysis of these types of diseases is that the detection of symptoms under real field conditions is erratic and can vary significantly from year to year depending upon environmental conditions and other factors (47). Interestingly, there was a significant association between pathogen application on pruning wounds (line 1) and increased mortality compared to results in untreated control plants (line 10) [ 2 (1) ϭ 19.4, P Ͻ 0.001].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this treatment was to hasten the onset of symptoms since one of the biggest disadvantages in the analysis of these types of diseases is that the detection of symptoms under real field conditions is erratic and can vary significantly from year to year depending upon environmental conditions and other factors (47). Interestingly, there was a significant association between pathogen application on pruning wounds (line 1) and increased mortality compared to results in untreated control plants (line 10) [ 2 (1) ϭ 19.4, P Ͻ 0.001].…”
Section: Discussionmentioning
confidence: 99%
“…Our experience demonstrated that these fungi could be reisolated 1 cm over the inoculation point, and incipient wood symptoms could be observed. The effectiveness of the inoculation was evaluated using the conventional method of fungus isolation (22), consisting of cutting six wood chips (approximate diameter of 1 to 2 mm and approximate length of 0.5 to 1 cm) that were placed on malt extract agar (MEA) plates (Merck, Darmstadt, Germany) and incubated at 25°C in darkness until fungi grew to a size at which they could be isolated and placed on PDA plates. As de- scribed above, the PDA plates were incubated and the colonies that grew were morphologically and/or molecularly identified.…”
Section: Pcr Conditions (I) Sybr Green Pcrmentioning
confidence: 99%
“…The occurrence of Phaeoacremonium spp. varies among grape-growing countries, with P. aleophilum the species most frequently found to affect grapevines worldwide (23,13,22). It was suggested that this pathogen disseminated from one host to another, such as kiwifruit and Prunus sp.…”
mentioning
confidence: 99%
See 2 more Smart Citations